47. Autonomic dysfunction in ALS patients: An early phase study_preliminary data. Issue 4 (April 2016) - Barbieri, F.; Bongiovanni, L.G.; Fabrizi, G.M.; Fondrieschi, L.; Monaco, S.
Abstract : Amyotrophic Lateral Sclerosis (ALS) is a fatal degenerative motoneuron disease. Since 40 years, study investigating a possible Autonomic Nervous System (ANS) involvement are reported. Although results are contradictory and studies difficult to compare, ALS appears not to be a single disease entity, but a spectrum of disorders involving mainly, but not only, motoneurons. The aim of the study was to investigate cardiovascular ANS function in ALS patients with low disability and normal respiratory function. We have included patients diagnosed with ALS according to El Escorial criteria, able to walk unaided. We excluded patients with swallowing difficulties, affected by autonomic dysfunction of other origin and taking ANS influencing drugs. We also excluded patients with respiratory insufficiency. Patients underwent cholinergic and adrenergic evaluations: SSR and standard autonomic tests during continuous monitoring of heart rate and blood pressure. We evaluated HRV, BRS and spectral analysis of HF and LF of RRI and BP. We compared patients with matched normal controls. We did not find any significant difference between groups, indicating a tendency toward a normal function of ANS in early phase of disease. We will expand our sample and possibily try a genotipic–phenotipic correlation, given the heterogeneity of ALS spectrum.